INOVASI DALAM PENGEFISIENSI AIR MELALUI PERANCANGAN STABILIZER REEL JUG - I Putu Wiradi Pradipta; I Ketut Yogi Swarandana (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2023)
Plastic is an important material in life, especially industry. The most widely produced plastic bottles in industry are polyethylene terephthalate plastic bottles. World PET production is used in synthetic fibers, and bottle production accounts for 30% of world demand. This is because of its strong mechanical properties, good resistance to chemicals and solvents. Ironically, environmental damage due to excessive energy exploitation and the current energy scarcity need to be addressed wisely. Energy efficiency needs to be carried out in an effort to minimize environmental damage. The purpose of this research is to determine water efficiency innovations carried out through designing reel jug stabilizers. The research results show that the reel jug stabilizer innovation results in gallon bottles being able to enter the filling chamber in a perpendicular position, so that they are parallel to the feeling water nozzle and become a superior product. It can be said that this innovation does not waste energy, especially water. In the usage range from February to September 2022, water savings of 224 m3 occur with production cost savings of IDR. 25.286.612.